2021
DOI: 10.1128/mbio.00167-21
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Uses a Host Stress Response To Balance the Elongation of Saturated/Monounsaturated and Polyunsaturated Very-Long-Chain Fatty Acids

Abstract: Stress and virus infection regulate lipid metabolism. Human cytomegalovirus (HCMV) infection induces fatty acid (FA) elongation and increases the abundance of lipids with very-long-chain FA (VLCFA) tails. While reprogramming of metabolism can be stress related, the role of stress in HCMV reprogramming of lipid metabolism is poorly understood. In this study, we engineered cells to knock out protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK) in the ER stress pathway and measured lipid changes using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…This endoplasmic reticulum-bound enzymatic process allows two carbons to the chain of long- and very-long-chain fatty acids (VLCFAs) per cycle. Elov 5 is also highly involved in the elongation of long-chain polyunsaturated fatty acids such as C18 and C20 PUFA [ 54 ]. It has been observed that under virus infection, Elov2, and specifically, Elov5, are highly activated and overregulate lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This endoplasmic reticulum-bound enzymatic process allows two carbons to the chain of long- and very-long-chain fatty acids (VLCFAs) per cycle. Elov 5 is also highly involved in the elongation of long-chain polyunsaturated fatty acids such as C18 and C20 PUFA [ 54 ]. It has been observed that under virus infection, Elov2, and specifically, Elov5, are highly activated and overregulate lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that under virus infection, Elov2, and specifically, Elov5, are highly activated and overregulate lipid metabolism. For example, the human cytomegalovirus (HCMV) infection induces fatty acid (FA) elongation and increases the abundance of lipids with very long-chain FA (VLCFA) tails by the activation of the Elov2 and Elov5 [ 54 ]. Specifically, it has been observed that the virus impacts the protein levels of ELOVL5, which elongates PUFAs through a PERK-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids were identified and quantitatively measured using ultra high-performance liquid- chromatography high-resolution tandem MS/MS (UHPLC-MS/MS) as recently described 69, 70 . Separation of lipids was done by reverse-phase chromatography using a Kinetex 2.6 µm C18 column (Phenomenex 00F-4462-AN) at 60°C using a Vanquish UHPLC system (Thermo Scientific) and two solvents: solvent A (40:60 water-methanol plus 10mM ammonium formate and 0.1% formic acid) and solvent B (10:90 methanol-isopropanol plus 10mM ammonium formate and 0.1% formic acid).…”
Section: Methodsmentioning
confidence: 99%
“…Lipids were identified and quantitatively measured using ultra high-performance liquidchromatography high-resolution tandem MS/MS (UHPLC-MS/MS) as recently described 69,70 .…”
Section: Lipidomics Sample Preparation Mass Spectrometry and Identificationmentioning
confidence: 99%
“…ER stress is often developed as a secondary mechanism to drug treatment or viral persistence. This is the case with HCMV [ 42 ], the hepatitis C virus [ 43 ], and the hepatitis B virus [ 44 ]. The infection of normal brain cells [ 45 , 46 ] and/or glioma cells [ 47 , 48 ] with retroviruses, NDV, or MDA-7/IL-24 also leads to ER modifications in cellular programming.…”
Section: Unfolded Protein Response (Upr): One Process Two Impactsmentioning
confidence: 99%